The waste-free world how the circular economy will take less, make more, and save the planet - Gonen, Ron. (New York Penguin, 2021)
Our take-make-waste economy has cost consumers and taxpayers billions while cheating us out of a habitable planet. But it doesn?t have to be this way. The Waste-Free World makes a persuasive, forward-looking case for a circular economic model, a ?closed-loop? system that wastes no natural resources. Entrepreneur, CEO and sustainability expert Ron Gonen argues that circularity is not only crucial for the planet but holds immense business opportunity.
Keywords: Industrial management--Environmental aspects